(untitled) (FAVE Sección Ciencias Veterinarias, 2022)
This study aims to account for the development of professional competences in Veteri-nary Medicine students involved in an International Student Exchanges. It was carried out with Veterinary Medicine students from Universidad Nacional del Litoral who participated in an International Student Mobility Program during 2019, and it analyzes the impact of student mobility on the formation of professional competences. The methodological strategy applied was the case study, where the quantitative and qualitative perspectives are combined. This triangulation allowed addressing the objectives of the study more adequately. Among the main contributions of the experience, it was found that it is a space where different teaching and learning processes favor the development of new competences in those who have the opportunity to participate in new education systems by approaching new cultures and languages, research projects and ways of knowledge circulation, thus enabling to broaden their horizons. Likewise, international academic mobility enables students to experience multiple situations in which they must employ various skills and attitudes.